TEOLOGI RAHIM MENURUT CHOAN SENG-SONG SUATU REFLEKSI KRITIS - Eramartina martina Saragih (Institut Filsafat dan Teknologi Kreatif Ledalero, 2022)
Abstract: The Asian reality is characterized by religious and cultural diversity. Social changes and especially poverty are the complexities they contain. In such circumstances, the Church is called to face this reality. Theologians are trying to find an understanding of theology that fits the Asian context. C.S. Song is an Asian theologian who tries to respond to this reality with a thought about the theology of Rahim that he explains using the narrative method.The theology of Rahim is a theology that guides humans to God's love and suffering and leads humans to freedom, justice and peace. The basic premise of Rahim's theology is contained in Passio: Passio as the starting point of theology, Rahim as Passio's